1997
DOI: 10.1254/jjp.75.65
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Antigen Inhalation-Induced Reproducible Early and Late Asthma in Guinea Pigs.

Abstract: ABSTRACT-To develop a model of chronic experimental asthma in guinea pigs, the animal was forced to inhale the mist of a low dose of ovalbumin (OA) adsorbed on fine Al(OH)3 for sensitization once every 4 weeks. The animal was challenged by inhalation with the mist of OA on day 14 after the respective sensitizations. Either the first or the second antigen challenge markedly induced an early asthmatic response (EAR), whereas there was hardly any late asthmatic response (LAR). At the 3rd challenge, LAR also emerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
18
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 27 publications
5
18
1
Order By: Relevance
“…Our previous animal model of asthma was developed by exposing guinea pigs to a fine mist of antigen solution. 13) However, it took more than 4 months to induce an LAR. Another key finding of the current study is that the EAR, LAR, and airway hyperresponsiveness were induced by the first antigen challenge, and took only 19 d, although only the EAR was induced after the first challenge in our previous model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous animal model of asthma was developed by exposing guinea pigs to a fine mist of antigen solution. 13) However, it took more than 4 months to induce an LAR. Another key finding of the current study is that the EAR, LAR, and airway hyperresponsiveness were induced by the first antigen challenge, and took only 19 d, although only the EAR was induced after the first challenge in our previous model.…”
Section: Discussionmentioning
confidence: 99%
“…However, approximately 20% of the mist trapped in the airway tissues was found to be deposited in the nasal mucosa despite using the glassware pressure nebulizer. 14) In addition, it took more than 4 months to induce the LAR through repeated the aerosols, 13) not particularly convenient for pharmacological examinations of anti-asthma drugs.…”
mentioning
confidence: 99%
“…injection with ovalbumin (OVA; 50 mg, Grade V; Sigma-Aldrich, St. Louis, MO, USA) adsorbed to alum (2 mg in 0.5 mL PBS) on days 0, 14 and 28. The alum was prepared as previously described (Nabe et al, 1997). Sensitized mice were challenged on days 35, 36, 37 and 40 under inhalation anaesthesia using isoflurane (Dainippon Pharmaceutical Co., Osaka, Japan) with 2% OVA administered i.t.…”
Section: Sensitization and Challengementioning
confidence: 99%
“…However, only the early bronchoconstrictive response was induced by OA inhalation in guinea pigs sensitized passively with anti-OA antiserum. Results of other studies (10,12,13), including our previous report (14), have also indicated that repeated antigen inhalation causes a biphasic asthmatic response. In contrast to the situation with lower airway obstructive responses, research on experimental models of allergic rhinitis has not been very extensive.…”
Section: Resultsmentioning
confidence: 64%